Numerical and Experimental Investigation of the Performance of Dynamic Wing for Augmenting Ship Propulsion in Head and Quartering Seas - Kostas Belibassakis; Evangelos Filippas; George Papadakis (Journal of Marine Science and Engineering, 2021)
Flapping-foil thrusters arranged at the bow of the ship are examined for the exploitation of energy from wave motions by direct conversion to useful propulsive power, offering at the same time dynamic stability and reduction of added wave resistance. In the present work, the system consisting of the ship and an actively controlled wing located in front of its bow is examined in irregular waves. Frequency-domain seakeeping analysis is used for the estimation of ship-foil responses and compared against experimental measurements of a ferry model in head waves tested at the National Technical University of Athens (NTUA) towing tank. Next, to exploit the information concerning the responses from the verified seakeeping model, a detailed time-domain analysis of the loads acting on the foil, both in head and quartering seas, is presented, as obtained by means of a cost-effective time-domain boundary element method (BEM) solver validated by a higher fidelity RANSE finite volume solver. The results demonstrate the good performance of the examined system and will further support the development of the system at a larger model scale and the optimal design at full scale for specific ship types.